Lectura, escritura y construcción del pensamiento crítico en estudiantes del quinto grado de educación primaria Institución Educativa Regina Leonor Cortes Alvarado, Nauta 2023 - Perez Saboya, Jaureman (2024)
The general objective of the thesis is to relate reading - writing with the construction of critical thinking in fifth grade students of Primary Education Regina Leonor Cortes Alvarado Nauta Educational Institution 2023. The type of quantitative descriptive research, with a cross-sectional correlational design, with a sample of 88 students from an educational institution in the Province of Loreto Nauta, the instruments for data collection were used an Evaluation Scale for the reading - writing variable and a Likert type scale to measure Critical Thinking. As a result, there is a Pearson correlation coefficient of rxy= 0.716, this value indicates a strong, direct and positive relationship between both variables; It is concluded by demonstrating the general hypothesis of the research: “There is a relationship between reading - writing with the construction of critical thinking of students in the fifth grade of primary education.